Positive leadership action framework: Simply doing good and doing well - Redín, D. M.; Meyer, M.; Rego, J. (Frontiers in Psychology, 2023)
This article presents the Positive Leadership Action Framework (PLAF) to structure Positive Leadership (PL). The novelty of the PLAF is that it incorporates the connections of PL to positive outcomes (financial and economic performance and social well-being) and organizational virtuousness. Also, it acknowledges its conditional nature on the virtues to achieve flourishing within the organization and society at large. We argue that the leader’s actions function as the engine for positive change within the organization, bridging the gap between individual virtues and organizational virtuousness and creating a feedback loop among both. To develop a positive organization, a leader needs to create positive assumptions among (and about) coworkers, positively impact the personal and professional development of employees, and balance positive formal and informal conditions at work. To do so, it is a sine qua non condition that the positive leader fosters his/her personal development by exercising the virtues and developing practical wisdom. In this way, the positive leader automatically provides followers with a vision of the final end towards the common good and achieves to set his/her organization on a pathway towards excellence.